ANALISIS NILAI-NILAI PENDIDIKAN AKHLAK TERHADAP TEMAN DALAM FILM ANIMASI NUSSA DAN RARA EPISODE COMPLICATION VOL. 11 - Anwar, Nurul Fauza; Zulfatmi, Zulfatmi; Realita, Realita (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Instilling moral values toward peers from an early age is essential in shaping children's character. One effective medium for internalizing these values is animated films that contain moral messages, such as NussadanRara. This study aims to identify the moral values toward peers presented in the “NussadanRara animated film, particularly in episode complication vol. 11”,danto analyze their relevance to verses of the Qur'an. This research uses a qualitative approach with a text study method. Data were collected through content analysis of the film using Charles Sanders Peirce’s semiotic approachdanthen correlated with Qur'anic verses. The findings reveal 14 moral values toward peers depicted in the film, including responsibility, modesty, mutual help, gratitude, honesty, apologizing, advising in goodness, generosity, cooperation in helping friends, respecting older peers, encouraging friends, correctingdanreminding peers, caring,danwelcoming friends openly. All of these values align with Qur'anic teachings that emphasize the importance of harmonious interpersonal relationships. Therefore, this film is suitable to be used as a medium for moral education.